A study of the radial and bending performance for poly (L‐lactic acid) braided stents with innovative runners. (29th July 2021) - Zhao, Gutian; Wang, Bin; Liu, Muqing; Tian, Yuan; Wu, Gensheng; Zhang, Yi; Cheng, Jie; Ni, Zhonghua
Abstract: Poly (L‐lactic acid) (PLLA) braided stent is expected to treat the peripheral vascular and biliary obstructive diseases with its excellent biocompatibility and biodegradability. However, the application of PLLA is still restricted by insufficient mechanical performance. In this paper, a series of PLLA braided stents with runners in axial, circumferential and spiral directions were prepared, and the effects of the runners on the mechanical performance of PLLA braided stents were studied. Meanwhile, the relationship between radial supporting performance and bending performance was analyzed to evaluate the effects on mechanical performance of PLLA stents. According to the relationship, it is found that the runners in different directions have a great influence on the mechanical performance of the stents. Especially the runners in spiral direction can effectively improve the radial force and bending stiffness of the stents compared with the control group. This work provides some suggestions for the development and design of PLLA braided stents in the future.